A invisibilidade da educação especial na socioeducação - Nascimento, Dinaira Rabelo do (Brasil, 2024)
This Course Completion Work is methodologically organized in a bibliographical and documentary research and has as its theme the articulation between special education and socio-education policies. The study seeks to identify whether the academic research points to the existence of some differentiated service for adolescents who are serving socio-educational measures and have been diagnosed with special educational needs. The project seeks to answer the following research problem: how have research investigated the presence of adolescents in conflict with the law who have special educational needs in the context of socio-education? To respond to the research problem, the general objective was initially focused on investigating whether there was any specific guidance for the care of adolescents with special educational needs when sanctioned with a socio-educational measure. However, during the investigation it became evident that the topic has not been effectively discussed, which forced the researcher to trace another path for the continuity of the studies and define another objective, that is, to identify whether the themes have been investigated in the postgraduate courses stricto sensu. The analysis is structured by the following specific objectives: to understand, through bibliographical and documentary research, the regulation and history of special education in Brazil, articulating the debate with the international context, verifying how the historical process of organization of special education took place ; to analyze the research collected in the CAPES Theses Bank on the subject; and, finally, to test an approximation between the fundamentals of special education and the follow-up of adolescents in the context of socio-education. The study concluded that the issue of socio-education, associated with the debate about adolescents in conflict with the law with special needs, is an invisible debate within the scope of academic research, which possibly indicates that it is also invisible within the scope of the execution of measures.